Uncertainty, Flourishing, and Existential Psychotherapy: Referencing Muhammad Iqbal's Model of Self - Khan, Abrahim H. (Toronto journal of theology, 2025)
This paper discusses an alternative way of thinking about self as a psychosocial dynamic process advanced by Muhammad Iqbal (1876-1935), a cosmopolitan philosopher-psychologist of Indo-Islamic heritage. His model of self is advanced here as a resource for an existential psychotherapy approach more hospitable for working with mental health clients of an Islamic cultural background than approaches informed by the existential thinking strand in a European philosophical tradition. Iqbal's model of the self is open to an understanding of truth and uncertainty as factors in how we live and think, and how we find or situate ourselves in the world. The sketch here of his model of self shows recognition that uncertainty is a necessary ingredient for health and wellbeing, and not merely an obstacle in self-identity forming.